Tibialis anterior tendon intrasubstance tear associated with anterior talofibular ligament tear: a rare encounter - Mohd Yazid B; Muhammad Iman A; Zubair AS; Sarah A; Irfan A; Muhammad Shazwan H (Pusat Perubatan Universiti Kebangsaan Malaysia, 2023)
Tibialis anterior (TA) tendon injury is an uncommon condition among other foot and ankle tendon pathology and there is insufficient literature on incomplete or intrasubstance TA tendon tear. To date, no cases of TA tendon injury with concurrent anterior talofibular ligament (ATFL) tear has been documented. This is a rare case of a 22-year-old gentleman with ankle injury following sports activity and magnetic resonance imaging (MRI) ankle showed incomplete TA tendon tear with concurrent ATFL tear. We proceeded with TA tendon direct repair and ATFL reconstruction. Patient showed good recovery and at third months, sixth months and 1-year post-surgery, American Orthopaedic Foot and Ankle Score (AOFAS) Ankle-Hindfoot scores were 86%, 90% and 96%, respectively. In TA tendon injury, incomplete tear or longitudinal split is reported mostly due to TA tendinopathy or degeneration. Early diagnosis followed by surgical treatment is shown to give better results, which can be either direct primary repair, tendon transfer or tendon reconstruction.